THE EVOLUTION OF CRITERIA FOR LIVER TRANSPLANTATION FOR HEPATOCELLULAR CARCINOMA: FROM MILAN TO SAN FRANCISCO AND ALL AROUND THE WORLD! - Ziogas, Ioannis A. (2017)
Introduction: Hepatocellular carcinoma (HCC) is the fifth most common malignancy and the third most common cancerrelated cause of death in the world. According to the stage of the disease, each patient is allocated to a different treatment option. Liver transplantation, along with surgical resection, is the only totally therapeutic option and is primarily indicated in HCC patients with underlying cirrhosis. However, the restricted number of liver grafts imposes difficulties in selecting the most suitable patients to receive those limited grafts and therefore certain criteria have been proposed. The Milan criteria are currently the most widely accepted and utilized criteria around the world, despite their restrictiveness. In an attempt to assist HCC patients exceeding them, but with a potential to display acceptable survival outcomes, undergo liver transplantation, research teams worldwide suggest expanded criteria based on their findings. Some of the most broadly known are the University of California, San Francisco (UCSF), Kyoto, Tokyo, Hangzhou and up-to-7 criteria. On the other hand, in order to expand the liver donor pool, grafts may be accepted from living, non-heart beating, elderly, steatotic, or even HCV-infected donors, in addition to the use of split livers with both advantages and disadvantages. The aim of this review is to thoroughly present the current situation of liver transplantation for HCC patients, with a focus on the criteria used and emerging challenges presented. Core tip: Hepatocellular carcinoma (HCC) is the third most common malignancy worldwide and liver transplantation represents the treatment of choice, particularly in the setting of cirrhosis. Lack of grafts led to the utilization of certain criteria in order to determine the eligibility of an HCC patient to access the waiting list. The most widely accepted are the Milan criteria, even though they are thought off as too restrictive. Consequently, transplant research groups all over the world published their own criteria, which showed acceptable outcomes. Living donor liver transplantation and other extended-criteria grafts have been proposed as an alternative to reduced donations. Ziogas IA, Tsoulfas G. The evolution of criteria for liver transplantation for hepatocellular carcinoma: from Milan to San Francisco and all around the world! DOI: https://doi.org/10.25176/RFMH.v17.n3.1195